Implementation of a Framework for Telerehabilitation in Clinical Care Across the Continuum During COVID-19 and Beyond. (January 2022) - Kim, Soo Yeon; Daley, Kelly; Pruski, April D.; AlFarra, Tariq; Azola, Alba; Gonzalez Fernandez, Marlis; Keszler, Mary S.; Friedel, Stacey; Haaf, Hayley; Segall, Harrison; Lien, Peiting; Cypher, Jacklyn; et al.
Abstract : Abstract: The COVID-19 pandemic has propelled an unprecedented global implementation of telemedicine and telerehabilitation as well as its integration into the healthcare system. Here, we describe the clinical implementation of the A3E framework for the deployment of telerehabilitation in the inpatient and outpatient rehabilitation continuum by addressing accessibility, adaptability, accountability, and engagement during the COVID-19 pandemic. By using an organized, coordinated, and stratified approach, we increased our telerehabilitation practice from 0 to more than 39, 000 visits since the pandemic began. Learning from both the successes and challenges can help address the need to increase access to rehabilitation services even beyond the COVID-19 pandemic.